The impact of embodied cognition on place attachment and supportive behavior toward historic buildings in heritage sites: exploring the moderating role of resident identity climate - Cai, Shuxiang; Hu, Yawen; He, Jingyi; Li, Kexiang (Frontiers in Psychology, 2025)
The development of tourism has driven profound transformations in heritage sites, and visitors‘ place attachment is widely recognized as playing a crucial role in local sustainable conservation. However, current research remains insufficient regarding the mechanisms through which visitors' embodied cognition influences place attachment and the impact of residents‘ identity climate perceptions within this process. This study integrates embodied cognition with the Cognitive-Emotional-Behavioral (CEB) framework, introducing place attachment as a mediating variable and residents' identity climate as a moderator of the social environment. It constructs an integrated embodied cognition-emotional-behavioral-moderator (ECEB-M) model to explore how cognitions generated during tourists‘ embodied experiences influence place attachment and their supportive behavior intentions. A field survey was conducted at the historic buildings of Quanzhou, a World Heritage site, collecting 383 valid visitor questionnaires. Research findings indicate that all three dimensions of embodied cognition—multisensory perception, physical engagement, and cognitive processing—exert positive effects on place attachment and intentions toward destination-supportive behaviors. Place attachment partially mediates the relationship between embodied cognition and intentions toward destination-supportive behaviors, while also positively influencing these intentions. Resident identity climate enhanced the influence of physical engagement and cognitive processing on place attachment, positively mediating the relationship between these factors and place attachment. Resident identity climate did not produce a significant moderating effect on the relationship between multisensory perception and place attachment. Therefore, tourists' cognitive processes in forming place attachment exhibit significant differences across distinct embodied experiences. This study aims to enrich research on embodied cognition and place attachment, offering valuable insights for the protection and management of historic buildings in heritage cities.